Management of Rhynchophorus ferrugineus Olivier in the Gulf and Mediterranean region - C. P. Ramachandran (International Coconut Community Journal, 2005)
The red palm weevil Rhynchophorus ferrugineus Olivier is the most deadly and dangerous pest of coconut, date, oil, sago and other palms. R. ferrugineus is distributed in over 33 countries over a wide range of area under different agro-climatic conditions and attacks more than two dozen palm species. In the Middle East the weevil is the most destructive pest of the date palms. The hidden nature of the pest attack makes timely detection of the infestation and control measures difficult. The earlier reviews provide details of biology and control methods viz. phyto-sanitary and preventive, curative, biological, baiting and trapping etc. Different combinations of above mentioned control methods have also been tried with varying degrees of success. Results of two major IPM programmes carried out in the gulf countries, the first during 1993-1998 mainly based on chemical and pheromone trapping and the second from 1998-2002 using bio-agents and pheromone trapping are discussed. In Jordan valley intensive pheromone trapping and incorporation of systemic insecticide in irrigation water could not control the pest even after three years. Development of ecofriendly pest control strategies like hybrid sterility, incompatibility and disruption of tolerance to high temperatures in Gulf and Mediterranean regions is suggested to combat the pest.